A world trade organization for the 21st century : the Asian perspective - Baldwin, Richard E.; Kawai, Masahiro, 1947-; Wignaraja, Ganeshan, 1962- (Cheltenham : Edward Elgar, 2014)
The global financial crisis exposed great shortcomings in the global economic architecture, generating extensive international debate about possible remedies for these deficiencies. The postwar global architecture was guided by major developed economies, centered around the IMF, the GATT, and the World Bank. Today, the balance of economic power is shifting toward emerging economies. Global governance and economic policy must reflect this shift. With contributions from prominent Asian and international trade experts, this book critically examines key changes occurring in the world trading system and explores policy implications for Asia.
1. Introduction and overview / Richard Baldwin, Masahiro Kawai and Ganeshan Wignaraja -- 2. WTO 2.0 : governance of global supply-chain trade / Richard Baldwin -- 3. Trade in value added : concept, development, and an East Asian perspective / Satoshi Inomata -- 4. Joining the supply chain : a firm-level perspective / Ganeshan Wignaraja -- 5. Effective industrial policies and global value chains / Patrick Low and Julia Tijaja -- 6. Mapping crisis-era protectionism in the Asia and Pacific region / Simon J. Evenett -- 7. Exchange rate policy and regional trade agreements : a case of conflicted interests? / Victor Pontines and Richard Pomfret -- 8. Policy challenges posed by Asian free trade agreements : a review of the evidence / Masahiro Kawai and Ganeshan Wignaraja -- 9. Constructing and multilateralizing the Regional Comprehensive Economic Partnership : an Asian perspective / Shujiro Urata -- 10. The ASEAN Economic Community : progress, challenges, and prospects / Siow Yue Chia -- 11. The future of the World Trade Organization / Biswajit Dhar -- 12. Plurilateral agreements : a viable alternative to the World Trade Organization? / Michitaka Nakatomi -- 13. The role of foreign direct investment flows and a possible multilateral agreement / Yunling Zhang and Rongyan Wang.
Includes bibliographical references and index.
Keywords: International finance